1) Given this Explicit formula, let's find a_1, and then a_2 and then compare both terms:
![\begin{gathered} a_n=2(-2x^2)^n \\ a_1=2(-2x^2)^1\Rightarrow a_1=-4x^2 \\ a_2=2(-2x^2)^2\Rightarrow a_2=2(4x^4)=8x^4 \\ a_3=2(-2x^2)^3\Rightarrow a_3=2(-8x^6)=-16x^6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/904w4ikzf5ly7ybf259fag9kngxwviu3sm.png)
2) Comparing both terms we can state that this is a Geometric Sequence we can write its ratio as:
![q=(8x^4)/(-4x^2)=-2x^2](https://img.qammunity.org/2023/formulas/mathematics/college/yx3mf0z8vtm3khvcu9m49fa9zhiib1i6ut.png)
3) So we can write our Recursive formula as:
![\begin{gathered} a_n=-2x^2* a_(n-1) \\ \text{Testing:} \\ a_2=-2x^2* a_1 \\ a_2=-2x^2*-4x^2 \\ a_{2=\text{ }}8x^4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/whufdllasonkqxwshqtqq56hu2ara6eajr.png)
So the answers are:
![\begin{gathered} a_1=-4x^2 \\ a_n=-2x^2* a_(n-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l7l9r97cj7nsigs5x6vhj17eoitqlrfqbq.png)